Population dynamics and net primary production of the aquatic macrophite Nymphaea rudgeana C. F. Mey in a lotic environment of the Itanhaém River basin (SP, Brazil) - Camargo, A. F. M. [UNESP]; FLORENTINO, E. R. [UNESP] (Instituto Internacional de Ecologia, 2000)
Neste trabalho, foi estudada a dinâmica populacional e estimada a produção primária líquida da macrófita aquática Nymphaea rudgeana em um braço do rio Itanhaém (Estado de São Paulo, Brasil). Esta espécie apresenta uma ampla variação anual de biomassa, em função da estação do ano, no local estudado. A partir do mês de novembro (13,1 g PS/m²), pode ser observado um aumento gradual da biomassa, atingindo o máximo em fevereiro (163,1 g PS/m²). Posteriormente, a biomassa diminui, mantendo-se em níveis baixos até um novo período de crescimento. A diminuição de biomassa está associada ao desenvolvimento de macrófitas flutuantes (Pistia stratiotes e Salvinia molesta) e, subseqüentemente, às condições ambientais desfavoráveis (valores de salinidade elevados) ao seu desenvolvimento. A produção primária líquida de N. rudgeana foi obtida a partir dos dados de biomassa e seu valor é estimado entre 3,02 e 3,82 t/ha/ano.

In this paper we evaluated the population dynamics and obtained estimates of the net primary production of the aquatic macrophyte Nymphaea rudgeana in an arm of the Itanhaém River (São Paulo State, Brazil). This species presents, in the studied area, a broad seasonal variation of biomass. As from November (13.1 g DW/m²) we observed a gradual increase of biomass that reached a maximum in February (163.1 g DW/m²). Then, the biomass decreased, maintaining low levels until a new growth period. The reduction of biomass is associated to the development of floating aquatic macrophytes (Pistia stratiotes and Salvinia molesta) and, subsequently to environmental factors (higher salinity values) that are unfavorable to their development. The net primary production of N. rudgeana was estimated from the biomass data, and the annual productivity value was estimated between 3.02 and 3.82 t/ha/year.
Dinâmica populacional e produção primária líquida da macrófita aquática Nymphaea rudgeana C. F. Mey em um ambiente lótico da bacia do rio Itanhaém (SP, Brasil)
Keywords: Macrófita aquática; Nymphaea rudgeana; dinâmica populacional; produção primária líquida; Brasil; Aquatic macrophyte; Nymphaea rudgeana; population dynamics; net primary production; Brazil